2011
DOI: 10.1016/j.taap.2010.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Signal transduction profile of chemical sensitisers in dendritic cells: An endpoint to be included in a cell-based in vitro alternative approach to hazard identification?

Abstract: The development of non-animal testing methods for the assessment of skin sensitisation potential is an urgent challenge within the framework of existing and forthcoming legislation. Efforts have been made to replace current animal tests, but so far no alternative methods have been developed. It is widely recognised that alternatives to animal testing cannot be accomplished with a single approach, but rather will require the integration of results obtained from different in vitro and in silico assays. The argum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…We could show that this pathway is a valuable cellular endpoint to detect the electrophilic skin sensitizers in vitro (Natsch 2010;Natsch and Emter 2008), a result later confirmed by several independent laboratories (Ade et al 2009;Johansson et al 2011;Megherbi et al 2009;Miyazawa and Takashima 2012;van der Veen et al 2013b;Vandebriel et al 2010). The accumulated transcriptome data indicate that it is actually the molecular pathway most widely and reproducibly upregulated by sensitizers (Neves et al 2011), and multiple Nrf2-dependent genes were identified as key marker discriminating sensitizers from non-sensitizers and irritants. The gene most consistently identified is HMOX1 (coding for heme oxidase), which was induced by sensitizers in at least eight independent studies, in vitro (Ade et al 2009;Arkusz et al 2010;Emter et al 2013;Johansson et al 2011;Neves et al 2013;van der Veen et al 2013b;Vandebriel et al 2010) and ex vivo (van der Veen et al 2014a).…”
Section: Activation Of the Nrf2 Pathwaysupporting
confidence: 60%
“…We could show that this pathway is a valuable cellular endpoint to detect the electrophilic skin sensitizers in vitro (Natsch 2010;Natsch and Emter 2008), a result later confirmed by several independent laboratories (Ade et al 2009;Johansson et al 2011;Megherbi et al 2009;Miyazawa and Takashima 2012;van der Veen et al 2013b;Vandebriel et al 2010). The accumulated transcriptome data indicate that it is actually the molecular pathway most widely and reproducibly upregulated by sensitizers (Neves et al 2011), and multiple Nrf2-dependent genes were identified as key marker discriminating sensitizers from non-sensitizers and irritants. The gene most consistently identified is HMOX1 (coding for heme oxidase), which was induced by sensitizers in at least eight independent studies, in vitro (Ade et al 2009;Arkusz et al 2010;Emter et al 2013;Johansson et al 2011;Neves et al 2013;van der Veen et al 2013b;Vandebriel et al 2010) and ex vivo (van der Veen et al 2014a).…”
Section: Activation Of the Nrf2 Pathwaysupporting
confidence: 60%
“…With regard to the complexity of the end point and the heterogeneity of compounds, more recent studies rather focus on the analysis and integration of multiple parameters, such as the holistic transcriptome. Because modifications at genomic and proteomic levels result from the coordination of different intracellular signaling pathways, the signal transduction profiles induced by chemicals in DCs could represent an extremely valuable end point to be included in a future in vitro test (reviewed in ref ). Among promising toxicity pathways, the activation of the Nrf2 antioxidant response element was recently proposed by Natsch and collaborators as a robust end point for detecting cysteine-reactive skin sensitizers. , The p38 MAPK signaling cascade is another pathway that has long been associated with the sensitizer-triggered maturation of DCs; , however, it was only recently viewed as a possible parameter for discriminating sensitizers from irritants .…”
Section: Introductionmentioning
confidence: 99%
“…Cells plated in six‐well plates (0.75 × 10 6 ml –1 , 2 ml per well) were treated with the selected drugs for 24 h. Briefly, as previously described by us (Neves et al ., ), RNA was extracted with TRIzol reagent, the concentration was measured by OD260 using a NanoDrop spectrophotometer (Thermo Scientific, Wilmington, DE, USA, USA) and samples were kept in RNA Storage Solution (Ambion, Foster City, CA, USA) at –80 °C until use.…”
Section: Methodsmentioning
confidence: 99%
“…NAD(P)H quinone oxireductase (NQO1) and hemeoxygenase 1 (HMOX1), which are detoxifying enzymes that eliminate harmful oxygen radicals from the cell (Ade et al, 2009;Natsch, 2010;Martin et al, 2011). As a consequence, there is activation of intracellular signalling pathways and nuclear transcription factors involved in DC maturation, as the p38 mitogen-activated protein kinase (p38 MAPK), nuclear factor kappa B (NF-κB) and activator-protein-1 (AP-1) (Takanami-Ohnishi et al, 2002;Matos et al, 2005a;Basketter & Maxwell, 2007;Neves et al, 2008Neves et al, , 2011. Some contact sensitizers also activate the NLRP3 inflammasome and caspase-1, involved in the secretion of IL1β, IL18 and IL33 (Martin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%